1999
DOI: 10.1016/s0893-133x(98)00131-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluoxetine on the Polysomnogram in Outpatients with Major Depression

Abstract: This study investigated the effects of open-label fluoxetine (20 mg/d)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 33 publications
2
30
1
1
Order By: Relevance
“…Disturbances in the rapid eye movement (REM) phase of sleep are characteristic of depressive patients, and it has been demonstrated that chronic administration of fluoxetine can improve this defect [76]. Interestingly, similar findings were obtained in preclinical research, where both acute [77] and chronic administrations of fluoxetine were effective in decreasing REM sleep in rodents [78].…”
Section: Effect On Depressive-like Behaviourmentioning
confidence: 60%
“…Disturbances in the rapid eye movement (REM) phase of sleep are characteristic of depressive patients, and it has been demonstrated that chronic administration of fluoxetine can improve this defect [76]. Interestingly, similar findings were obtained in preclinical research, where both acute [77] and chronic administrations of fluoxetine were effective in decreasing REM sleep in rodents [78].…”
Section: Effect On Depressive-like Behaviourmentioning
confidence: 60%
“…This finding is perhaps not surprising, as there are studies using objective polysomnographic indices finding that a proportion of SSRI-treated patients experience a disturbance of their sleep, 68 and these objective sleep problems can last as long as 30 weeks after SSRI discontinuation. [68][69][70][71] Thus, there were subjective improvements reported by many of those on antidepressants but an objective worsening if the antidepressant was paired with sleep hygiene (i.e., CBT-I was not used). Given the widespread use and belief that sleep hygiene is effective, 57 this finding suggests antidepressants should not be augmented with sleep hygiene if improved objective sleep is desired.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was still significant when controlling for maternal mood and comparing antidepressant-exposed children to children born to women with major depressive disorder (Casper et al, 2003). Sleep has also been considered to be modulated by prenatal SRI exposure, because a known side effect of current SSRI use is disruption of normal sleep patterns (Sharpley and Cowen, 1995;Trivedi et al, 1999). A study using median and higher doses of SRIs observed increased fetal motor activity in first and second trimesters compared with control or unmedicated, depressed mothers.…”
Section: H Behavioral Studies In Neonates and Childrenmentioning
confidence: 99%